Devonian plutons in southeastern Cape Breton Island, Nova Scotia - Barr, Sandra M.; MacDonald, Alan S. (Atlantic Geology, 1992)
Four granitic plutons and a suite of granitic dykes of Devonian age occur in the Mira (Avalon) Terrane of southeastern Cape Breton Island. Granodiorite gradational to granite in the Lower St. Esprit pluton is chemically distinct from and unlikely to be genetically linked to comparable units in the other plutons. The Salmon River pluton consists of highly evolved rhyolite porphyry and is also not likely to be genetically linked to the other units. In contrast, the Gillis Mountain and Deep Cove plutons and.the Blue Mountain dykes are interpreted to be co-genetic and possibly co-magmatic on the basis of chemical continuity among their units, which range in composition from quartz monzodiorite to granite and rhyolite porphyry. They have I-type petrographic and chemical features, whereas the Lower St. Esprit has some M-type characteristics and the Salmon River rhyolite porphyry appears transitional between felsic I-type and A-type granites. Cu-Mo mineralization is associated with the Gillis Mountain pluton, and polymetallic Cu-Mo-Pb-Zn-Bi-Ag mineralization with greisen zones in the Deep Cove pluton and with skarn in the Blue Mountain contact metamorphic aureole. Minor Cu-Zn mineralization occurs adjacent to the Lower St. Esprit pluton, although a definite genetic relationship with thc pluton has not been established. Trace Pb mineralization has been reported from the Salmon River pluton. The origin of these Devonian plutons is uncertain, but is postulated to have been linked to regional strike-slip faulting and extension. RÉSUMÉ Quatre plutons granitiques et une suite de dykes granitiques d'âge Dévonien giseent dans le terrain de Mira (Avalon) du sud-est de l'ile-du-Cap-Breton. La granodiorite, en transition avec du granite, du pluton de Lower St-Esprit est chimiquement distincte et n'est probablement pas reliée génétiquement aux unités comparables des autres plutons. Le pluton de la rivière Salmon consiste en une rhyolite porphyrique ...